2014
DOI: 10.2118/167698-pa
|View full text |Cite
|
Sign up to set email alerts
|

Imbibition and Water Blockage In Unconventional Reservoirs: Well-Management Implications During Flowback and Early Production

Abstract: Driven by field logistics in an unconventional setting, a well may undergo weeks to months of shut-in after hydraulic-fracture stimulation. In unconventional reservoirs, field experiences indicate that such shut-in episodes may improve well productivity significantly while reducing water production. Multiphase-flow mechanisms were found to explain this behavior. Aided by laboratory relative permeability and capillary pressure data, and their dependency on stress in a shale-gas reservoir, the flow-simulation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
77
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(85 citation statements)
references
References 14 publications
3
77
0
1
Order By: Relevance
“…10 shows the simulation results that the water imbibition through well shut-in can reduce the water saturation beside the fracture Table 2. The evaluated and predicated performance of 10 fractured wells in Niobrara shale oil play (Yuan et al, 2016a after hydraulic fracturing, which will benefit the production (Bertoncello et al, 2014). Spontaneous imbibition conducts different influence to gas production.…”
Section: Gas Recovery By Spontaneous Imbibitionmentioning
confidence: 99%
“…10 shows the simulation results that the water imbibition through well shut-in can reduce the water saturation beside the fracture Table 2. The evaluated and predicated performance of 10 fractured wells in Niobrara shale oil play (Yuan et al, 2016a after hydraulic fracturing, which will benefit the production (Bertoncello et al, 2014). Spontaneous imbibition conducts different influence to gas production.…”
Section: Gas Recovery By Spontaneous Imbibitionmentioning
confidence: 99%
“…Roychaudhuri et al (2011) pointed out that, on the basis of shale gas reservoir development practices, a shale gas well has a high yield at low flowback rate; this phenomenon is closely related to SI in reservoirs. Bertoncello et al (2014) found that SI is strongly related to fluid loss in reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 The mechanism of water transport into formation matrix and modeling remains difficult to explain in unconventional formation, although the interaction between fracturing fluids and formation has been extensively studied 12,13 in recent years given the specific characteristics of unconventional formation, such as ultralow permeability, strong heterogeneity, and complex mineral composition. [14][15][16][17] Spontaneous imbibition is a dominant mechanism of water transport into formation considering the high capillary pressure in nanopores. [18][19][20][21] A research development of spontaneous imbibition is summarized systematically, and the main models include Lucas-Washburn, Terzaghi, Handy, Mattax and Kyte, and Aronofsky.…”
Section: Introductionmentioning
confidence: 99%